Model of Using Tiktok’s UGC as a New Media Political Communication Strategy for The 2024 Presidential Election in Indonesia - Prabu Revolusi (Greenation Research & Yayasan Global Resarch National, 2023)
This research explores the use of TikTok as a new tool for political communication strategy in the context of the 2024 Presidential Election in Indonesia, focusing on the User Generated Content (UGC) model and the role of